Open comparisons of social services in Sweden—Why, how, and for what? - Trygged, Sven (Cogent social sciences, 2017)
Open Comparisons is a soft power governance method using data collected from the municipalities for benchmarking their activities. Open Comparisons in Sweden may have different national goals, such as to measure quality, policy development and democratic openness. The overall aim of this paper is to describe and analyze the use of Open Comparisons to monitor the social welfare services—social assistance, child and youth care, and treatment of alcohol and drug abuse. Four focus group interviews were carried out with professionals from eight municipalities. Results show that Open Comparisons measures the technical quality of activities by reviewing what is available, such as routines and agreements, but says little about trickle down to client level. The findings are discussed in a wider context of overall goals of Open Comparisons related to soft power governance and governmentality which includes how the social services may internalize this way of thinking.